Ethanol combined with energy drinks: Two decades of research in rodents - Petribu, Beatriz Nunes; Abrahao, Karina Possa; Souza-Formigoni, Maria Lucia Oliveira (Frontiers in Behavioral Neuroscience, 2023)
Many studies raised concerns on alcoholic beverages consumption mixed with energy drinks (AmED), which can induce higher rates of binge drinking and earlier development of alcohol use disorders. After 20 years of research, few studies with laboratory animals have focused on the effects of this mixture and the neurobiological and pharmacological mechanisms underlying them. We found 16 articles on AmED administration to rodents evaluating its effects on voluntary consumption, locomotion, anxiety-like behavior, memory, influence on the onset time of seizures, biochemical and neurochemical measures. Some of these studies indicated energy drinks (ED) can alter the pattern of use and motivation to consume ethanol (EtOH); increase the expression of sensitization to EtOH stimulant effect and the proportion of sensitized mice; decrease the aversiveness of high concentrations of EtOH, among other effects. In addition AmED hastens the loss of righting reflex and its effects on memory are controversial. After acute administration no difference was found in blood ethanol concentration (BEC) of rodents which received EtOH with or without ED, but after 60 days of treatment, AmED group had lower BEC levels than EtOH group. Data on biochemical and neurochemical parameters after AmED are not consistent. Although the AmED group presented higher glucose levels than the EtOH group when drugs were administered by gavage, this was not observed in a self-administration protocol. AmED may induce higher kidney damage, higher levels of plasma urea, uric acid and creatinine when compared to EtOH. Chronic consumption of AmED causes an inflammatory response and oxidative stress, which may induce cell death in the cortex and hypothalamus of adult rats. These controversial results show that AmED diverse effects depend on sex, age and lineage of the animals, duration of the treatment and route of administration. Further research is necessary to evaluate the mechanisms underlying AmED biological effects.